If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(w+)+4w=3(2w-1)=8
We move all terms to the left:
2(w+)+4w-(3(2w-1))=0
We add all the numbers together, and all the variables
2(+w)+4w-(3(2w-1))=0
We add all the numbers together, and all the variables
4w+2(+w)-(3(2w-1))=0
We multiply parentheses
4w+2w-(3(2w-1))=0
We calculate terms in parentheses: -(3(2w-1)), so:We add all the numbers together, and all the variables
3(2w-1)
We multiply parentheses
6w-3
Back to the equation:
-(6w-3)
6w-(6w-3)=0
We get rid of parentheses
6w-6w+3=0
We add all the numbers together, and all the variables
3!=0
There is no solution for this equation
| 5x-3(-x+12)=52 | | x-5=4x+10= | | 12x-53+180-10x-23=180 | | N=96=n | | 4a+2=5,2 | | 21+2r=4(3r-2)-1 | | 25=24+x2 | | 2(2x+5)=3(22-x | | 17+r/2-20=14 | | 3/2x+4+3/2x+4+1/5x+9=180 | | 3.6w=1.6w=24 | | 12=3r+4,5 | | (x+8)=4 | | 60-9y=24 | | 7.5=2.5/x | | 3x=-5x+22 | | 129=12b=15 | | 24-8x=-3(4x-2)-6 | | -b-18=-28 | | 0=-16x^2+32x+9 | | -6=4x-8 | | 20r=-18+18r | | 6m+1=2m+1 | | X/2+4/2=9-3x | | 10x+8=3(x–2) | | b/12+4=12 | | y²+4y-6=0 | | 1 = v+786 | | 2(x-3)+4(x+5)=6x | | -11+5=3y | | 7(g+6)=56 | | n-3=12÷3 |